2019
DOI: 10.1080/14712598.2019.1606209
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibition for the treatment of mesothelioma

Abstract: Introduction: Combination chemotherapy is currently standard care for advanced mesothelioma. Checkpoint blockade is a promising new treatment. Areas covered: This review covers clinical use and biomarkers of checkpoint blockade. Medline search used keywords 'mesothelioma' combined with 'checkpoint blockade' OR 'PD-L1' OR 'PD1' OR 'anti-CTLA4'; the search terms AND 'clinical trial' or AND 'biomarker*' were added. Handsearching covered abstracts from relevant meetings from 2016-2018 and reference lists. Data inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 84 publications
1
13
0
2
Order By: Relevance
“…A previous study has shown that some patients with sarcomatoid MPM, who responded to nivolumab show high TPS of PD‐L1 (>50%), which is similar to the case described here . Regarding the sarcomatoid type, several studies using ICIs for refractory MPM examined a small number of cases and found that the efficacy of PD‐L 1 expression status as a predictive biomarker for the response to nivolumab may be limited . Several chemotherapies may not have sufficient effects and may deteriorate the general condition in cases of sarcomatoid MPM.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study has shown that some patients with sarcomatoid MPM, who responded to nivolumab show high TPS of PD‐L1 (>50%), which is similar to the case described here . Regarding the sarcomatoid type, several studies using ICIs for refractory MPM examined a small number of cases and found that the efficacy of PD‐L 1 expression status as a predictive biomarker for the response to nivolumab may be limited . Several chemotherapies may not have sufficient effects and may deteriorate the general condition in cases of sarcomatoid MPM.…”
Section: Discussionsupporting
confidence: 86%
“…34 The cut-off levels of PD-L1 positivity vary among trials. 35 Considering that the positive rates were reported from different small studies with a small number of accrued patients, the data may be limited and actual rates of expression have hardly been studied. In addition to this, whether the ICI efficacy is truly dependent on the PD-L1 expression level is still controversial.…”
Section: Open Accessmentioning
confidence: 99%
“…5,6 Most recently, antibodies targeting immune checkpoints have been studied in MPM. 7 Although the anti-CTLA-4 antibody tremelimumab was not effective in a randomized trial, 8 it appears that responses to the anti-PD-1 antibody, pembrolizumab, can be seen iñ 20-30% of MPM. 9 Given this encouraging data, it is becoming increasingly important to fully understand the mesothelioma immune microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%